Accounting for biogenic carbon and end-of-life allocation in life cycle assessment of multi-output wood cascade systems. (1st December 2020) - Garcia, Rita; Alvarenga, Rodrigo A.F.; Huysveld, Sophie; Dewulf, Jo; Allacker, Karen
Abstract: Wood cascade systems composed of products with long service lives can contribute to carbon storage, resource efficiency and circular economy. The environmental assessment of such multi-output systems is however challenging due to (i) multiple products and recycling steps, and (ii) the distribution of emissions, particularly of biogenic CO2, over long time spans. In Life Cycle Assessment (LCA), the former is usually dealt through end-of-life (EoL) allocation methods, while the latter is assessed via biogenic carbon accounting (BCA) methods. This article aims to assess how different BCA and EoL allocation methods may influence the LCA results of wood cascade systems, particularly their biogenic carbon footprint (BCF), both at supply chain and product levels. Six BCA methods and five EoL allocation methods were analysed, combined and applied to a wood cascade system delivering multiple products: (1) flooring, (4) particleboard (PB) and (5) electricity (reference flow: 1 m 3 wood). At supply chain level (prior to the application of EoL allocation methods), distinct BCFs were obtained ranging from −211 to +52 kgCO2 eq/m 3 of wood (as input). At product level, when applying the different EoL allocation methods, the variability further increased. For instance, the BCF of PB ranged from −5.61 to +0.04 kgCO2 eq/kgPB; while the BCF of electricity ranged from −0.50 to +0.39 kgCO2 eq/kWh (considering results within the 25–75 percentiles). Other factors influencing the results were the assumptions regarding the timing of forest growth, the stage in the cascade chain, the recycling content and the EoL scenario. A proper understanding of the influence of the BCA and EoL allocation methods and their assumptions on the BCF of wood cascading products is key, especially for countries/regions promoting a circular economy. Highlights: Biogenic carbon accounting and EoL allocation methods compared in wood cascade LCA. Results are presented at supply chain and product level, with numerous scenarios. Methods largely influence results ranging from climate benefits to climate burdens. Understanding the method's influence on LCA results is key to support policymaking.